Fluid synergy tourist route enhnacement through networking of distinations and landscape development of access corridors : Norzagaray, Bulacan in focus - Villanueva, Mary Claire C. (College of Architecture, University of the Philippines Diliman, 2007)
This study attempts to provide a study framework on how to provide an attractive context for the tourism destinations in an area. The needs and preferences of potential tourists are identified through a survey and a study site is chosen and evaluated. The findings from basis of a landscape devel;opment plan of a network of tourist corridor that will not only offer basic roadway amenities, but will also positively showcase the landscape character of the chosen site. A cost-benefit analysis is made to present the economic viability of the proposed physical improvements of access corridors. The formulated guidelines are aimed to suggest ways and means to local government units, tourism authorities, planners and designers on how to develop tourist destinations while incorporating environmental context through scenic enhancement context through scenic enhancement of corridors.